2021
DOI: 10.3390/jcm10163640
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Psoriasis and Prevalence of Cardiovascular Disease in 88 Japanese Patients

Abstract: Psoriasis is a systemic inflammatory disease known to affect survival in the presence of cerebral or cardiovascular comorbidities. However, no clear guidelines have been defined regarding the extent of vascular lesion testing that should be performed in patients with psoriasis. We therefore performed coronary computed tomography angiography (CCTA) in 88 Japanese patients with psoriasis who visited Kansai Medical University Hospital between 2015 and 2019 and determined the ankle–brachial pressure index (ABI) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…CCTA abnormalities were identified and compared to healthy controls. In the patients with abnormal results for both ABI and CCTA, the rates of CCTA vascular lesions were significantly higher, also revealing a correlation between CCTA and ABI in psoriasis patients [13].…”
mentioning
confidence: 74%
“…CCTA abnormalities were identified and compared to healthy controls. In the patients with abnormal results for both ABI and CCTA, the rates of CCTA vascular lesions were significantly higher, also revealing a correlation between CCTA and ABI in psoriasis patients [13].…”
mentioning
confidence: 74%
“…Using CCTA, we previously reported that cardiovascular abnormalities were more common in 88 Japanese patients with psoriasis before the use of biologic agents than in healthy controls [8]. However, CCTA is not a simple test, even though it is effective in detecting cardiovascular involvement in psoriasis.…”
Section: Methodsmentioning
confidence: 99%
“…The blood coronary arteries and abdominal aorta in particular have been measured in a few studies to shed light on the most vulnerable areas that might lead to sudden all-cause death as well as cause-specific death [5][6][7]. Using CCTA, we previously reported that cardiovascular abnormalities were more common in 88 Japanese patients with psoriasis before the use of biologic agents than in healthy controls [8]. However, CCTA is not a simple test, even though it is effective in detecting cardiovascular involvement in psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…This is followed by the formation of an atherosclerotic plaque that causes reduction or closure of blood flow through the vessel (usually by plaque rupture), leading to myocardial infarction or stroke (Figs. 2, 3) [28].…”
Section: Atherosclerosismentioning
confidence: 99%